2014
DOI: 10.1155/2014/828137
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Biobran, Modified Arabinoxylan Rice Bran, in Improving Symptoms of Diarrhea Predominant or Mixed Type Irritable Bowel Syndrome: A Pilot, Randomized Controlled Study

Abstract: Background. Recently, it was revealed that low grade mucosal inflammation and/or immune imbalance of the lower digestive tract is one of the mechanisms involved in symptom generation in patients with irritable bowel syndrome (IBS). Biobran, arabinoxylan compound derived from rice bran, has been reported to have several biological actions such as anti-inflammatory and immune modulatory effects. So we investigated the therapeutic effects of Biobran in patients with IBS. Method. Forty patients with diarrhea predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…The updated systematic review and meta-analysis on fiber in IBS performed for this guideline identified 15 RCTs, involving 946 patients (58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72). Only one trial was at low risk of bias (70).…”
Section: Quality Of Evidence: Moderatementioning
confidence: 99%
“…The updated systematic review and meta-analysis on fiber in IBS performed for this guideline identified 15 RCTs, involving 946 patients (58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72). Only one trial was at low risk of bias (70).…”
Section: Quality Of Evidence: Moderatementioning
confidence: 99%
“…It was also shown to have anti-inflammatory effects, with observed protective actions in acute liver injury in rats [29] and improvement effects on chronic rheumatism [30] and IBS [31] in humans.…”
Section: Discussionmentioning
confidence: 99%
“…; Kamiya et al . ). Phenolic compounds show great potential to treat cancer and prevent oxidation in our body (Huang et al .…”
Section: Introductionmentioning
confidence: 97%
“…Rice bran is also beneficial to lower the blood cholesterol level, blood glucose level and blood pressure (Prasad et al 2011). Moreover, such bran serves as anticancer, anti-aging and anti-inflammatory agents as it is a rich source of phenolic antioxidants (Prasad et al 2011;Esa et al 2013;Kamiya et al 2014). Phenolic compounds show great potential to treat cancer and prevent oxidation in our body (Huang et al 2010).…”
Section: Introductionmentioning
confidence: 99%